2016
DOI: 10.11113/.v78.5774
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis on the Application of Eia Process in Malaysia

Abstract: Environmental Impact Assessment (EIA) has been introduced in Malaysia as an interactive planning tool since 1976 through the Environment Quality Act (EQA) 1975. The implementation of the EIA process in Malaysia has played a significant role in cultivating environmental protection and sustainable development practice in Malaysia. This paper focuses on the EIA process that is being implemented in Malaysia in ensuring effective application of EIA. The purpose of this paper is to present the research findings that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Meanwhile, it is important to predict the impacts on the environment of the proposed project and effective measures to reduce such impacts by adopting the Environmental Impact Assessment (EIA) into the framework. EIA has been adopted as an interactive planning tool in Malaysia since 1976 through the Environment Quality Act (EQA) 1975 [ 39 ]. In Malaysia, there are two types of EIA procedures adopted–Preliminary EIA and the Detailed EIA (DEIA).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meanwhile, it is important to predict the impacts on the environment of the proposed project and effective measures to reduce such impacts by adopting the Environmental Impact Assessment (EIA) into the framework. EIA has been adopted as an interactive planning tool in Malaysia since 1976 through the Environment Quality Act (EQA) 1975 [ 39 ]. In Malaysia, there are two types of EIA procedures adopted–Preliminary EIA and the Detailed EIA (DEIA).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Li et al (2012), Maidin (2011) and Omar & Leh (2009) has collectively agreed that the public participation held for the Second Schedule activities were ineffective due to the rise of environmental issues in Malaysia. Additionally, the public participation administered for EIA are frequently applied late where the decisions have already been decided (Makmor and Ismail, 2016b;Alam, 2014). From a study by Makmor and Ismail (2014), the author concluded that ineffective public participation is also contributed by the attitude of each stakeholder in the process of EIA namely the consultants, the project proponents and also the public.…”
Section: Introductionmentioning
confidence: 99%